Validity Of Congo Red Agar And Modified Congo Red Agar To Detect Biofilm Of Enterococcus Faecalis - Rina Normanita (Universitas Muhammadiyah Malang, 2020)
Purpose: Enterococcus faecalis causes nosocomial infections such as bacteremia, urinary tract infections, intra-abdominal infections, and endocarditis. These infection is associated with biofilm and intrinsically resistant to many antibiotics. This study aims to determine the validity of the CRA and MCRA for detecting biofilms of Enterococcus faecalis Method: This is a laboratory observational study with 30 sample of Enterococcus faecalis. We performed biofilm examination for Enterococcus faecalis by using Congo red Agar, Modified Congo red Agar and Microtitter Plate Assay as gold standard. Result: Both MCRA and CRA were compared MPA as a gold standard was obtained p value is 0.309 (p> 0.05), with a Kappa agreement coefficient is 0.067, which indicates there is no significant agreement to detect biofilm of Enterococcus faecalis. MCRA and CRA have almost no compatibility with MPA for biofilm forming of Enterococcus faecalis. Conclusion: Both MCRA and CRA has a very high sensitivity (100%), but the specificity is very low 6.67% for detecting the biofilms of Enterococcus faecalis. MCRA and CRA can not determine negativity well and it have a high false positive rate, so to increase specificity of biofilm forming, we must combine these method with the others. Keywords: Biofilm, Enterococcus faecalis, CRA, MCRA, MPA.